The paradox of representation : racial gerrymandering and minority interests in Congress - Lublin, David, 1968- (Princeton University Press, 1997)
"In The Paradox of Representation, David Lublin offers an unprecedented analysis of a vast range of rigorous, empirical evidence that exposes the central paradox of racial representation: Racial redistricting remains vital to the election of African Americans and Latinos but makes Congress less likely to adopt policies favored by blacks. Lublin's evidence, together with policy recommendations for improving minority representation, will make observers of the political scene reconsider the avenues to fair representation." "The author proposes that establishing a balance between majority-minority districts and creating districts where the minority population would be slightly more dispersed, making up 40 percent of a total district, would allow African Americans to exercise more influence over their representatives."--Jacket